SYNTHESIS AND CHARACTERIZATION OFA NEW ELECTRODE MATERIAL : IODINE + VINYL PYRIDINE (I2 + VP) - Mardiyanto Mardiyanto; E. Kartini; Supandi S. (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
SYNTHESIS AND CHARACTERIZATION OFA NEW ELECTRODE MATERIAL : IODINE + VINYL PYRIDINE (I2 + VP). Iodine is one of the electrode materials in a silver solid state battery. However, a serious problem is still found when it is used as an electrode in a battery system because iodine is a very reactive element and will react with water vapor which ionizes it to form I- . This ion then combines with I2 to become I3- which has dark brown colour and it is very corrosive material. From the engineering point of view, it is very difficult to isolate the iodine electrode from the room atmosphere although an aluminum casing is used. The use of mixed iodine-vinyl pyridine (I2-VP) was researched. The mixed iodine-vinyl pyridine was no longer reactive those from the EDAX results show that the iodine is still available in the mixed iodine- vinyl pyridine powder ( more than 95 %). The total electronics and ionic conductivity of the mixed iodine- vinyl pyridine powder was measured by LCR meter and found that value of 3 S/cm at low frequency. However, the OCV of one cell battery (silver/electrolyte/I2-VP) was only 0.1 volt.